FEASIBILITY STUDY: A SOLUTION TO PROJECT VIABILITY - Eneje, Linus Chukwudi (Advanced Journal of Environmental Sciences (AJES), 2024)
This paper explores the significance of feasibility studies in ensuring the viability and sustainability of projects, particularly in the construction industry. It highlights that uncertainties are an inherent part of projects, but proper feasibility studies can mitigate risks and enhance project outcomes. The study emphasizes that project sustainability is closely linked to a thorough feasibility analysis, involving various stakeholders like clients, contractors, suppliers, and regulatory bodies. The paper defines a feasibility study as a critical tool for determining whether a project is technically, legally, and economically viable. It also discusses different types of feasibility studies marketing, technical, legal, environmental, and financial and outlines the components required for a comprehensive analysis. Furthermore, the work stresses the importance of involving professionals such as architects, engineers, and consultants in the feasibility study process to ensure the incorporation of sustainable practices and materials. The study concludes that a well-executed feasibility study is essential for the success of a project, particularly in developing countries like Nigeria, where construction activities are rapidly expanding. It argues that such studies should not only focus on financial aspects but also consider environmental and social impacts to achieve long-term sustainability.